Collective Intrahousehold Labor Supply in Europe: Distribution Factors and Policy Implications - Ignacio Belloc; Jorge Velilla (Journal of Family and Economic Issues, 2024)
This paper analyzes how variables that shape intrahousehold bargaining relate to spouses' labor supply. We estimate a collective model using data from the EU-SILC over 2004–2019 for 17 countries. Results provide evidence of the relevance of the following distribution factors: sex ratio, non-labor income, age difference, education difference, and fertility rates. The sex ratio seems to be a distribution factor in Czech Republic, Denmark, Hungary, Ireland, Italy, Poland, Spain, and Switzerland. In addition, the wife's share of non-labor income is a distribution factor in Belgium, Czech Republic, Estonia, Ireland, Italy, Luxembourg, Poland, Portugal, Spain, and the UK. In Austria, Belgium, Czech Republic, Denmark, Estonia, France, Ireland, Italy, Luxembourg, Switzerland, and the UK the spouses' age gap displays opposite signs on spouses' labor supply, whereas in Austria, Belgium, Czech Republic, Denmark, France, Hungary, Ireland, Luxembourg, Portugal, and the UK the spouses' education level differences display intrahousehold bargaining signs. Finally, the fertility rate is a distribution factor in Austria, Czech Republic, Denmark, Estonia, France, Ireland, Latvia, Portugal, Switzerland, and the UK. These results indicate that spousal- and country-specific characteristics are assessed differently across Europe and may help planners to implement household policies on cash transfers, schooling, and fertility.
Keywords: D13; J22; H31; 300; Household labor supply; Collective model; Distribution factors; EU-SILC